PENGARUH PENGENALAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP KESEHATAN ANAK USIA DINI DI MASA PANDEMI COVID-19 - Retyan Kristanti; Elisa Novie Novie Azizah; Narendra Kusumastuti (Universitas Islam Lamongan, 2021)
Abstract This study aims to determine the effect of distance learning This study aims to: 1) introduce the 7 steps to wash hands properly in group B TK Dharma Wanita Watualang 1 Ngawi. 2) knowing the problems in the physical aspects of motoric 7 steps washing hands in group B TK Dharma Wanita Watualang 1 Ngawi. The research used is quantitative research. The subjects of this study were children of group B TK Dharma Wanita Watualang 1 Ngawi, with a total of 23 students. Data collection methods used in this study are observation and documentation. This research was conducted using a One-Group Pre-Test Post-Test model consisting of a Pre-Test (before being given treatment) and Post-Test (after being given treatment). Furthermore, based on the results of research based on data analysis, it was found that there was an increase in the average score of the physical motor skills of group B children before and after being given the treatment, namely from 47.8 to 63.86. Furthermore, from the results of the calculation of the t-test formula for a small sample that is interconnected in this study, it shows that tcount> ttable (7.7> 1.7), with a significance level of 5%. Based on the results of the study, the authors conclude that there is an effect of the introduction of clean and healthy living behaviors (PHBS) on children's health during the COVID-19 pandemic group B TK Dharma Wanita Watualang 1 Ngawi.